2020
DOI: 10.1103/physrevb.102.075425
|View full text |Cite
|
Sign up to set email alerts
|

Electron transport properties of graphene nanoribbons with Gaussian deformation

Abstract: Gaussian deformation in graphene structures exhibits an interesting effect in which flowershaped confinement states are observed in the deformed region [Carrillo-Bastos et al., Phys. Rev. B 90 041411 (2014)]. To exploit such a deformation for various applications, tunable electronic features including a bandgap opening for semi-metallic structures are expected.Besides, the effects of disorders and external excitations also need to be considered. In this work, we present a systematic study on quantum transpor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 61 publications
1
14
0
Order By: Relevance
“…Bumps are often observed in graphene samples and can be artificially induced, for example, by pinning graphene on patterned substrates [40,41] or by thermally inducing a buckling transition [42]. In the absence of magnetic field, such a system has been widely investigated in the literature [43][44][45][46][47], with focus on both electronic structure and transport properties in 2D graphene and graphene ribbons or dots. Here, we focus on the case of periodic bumps with a Gaussian profile similar to that of ref.…”
Section: Periodic Bumped Graphene Superlatticementioning
confidence: 99%
“…Bumps are often observed in graphene samples and can be artificially induced, for example, by pinning graphene on patterned substrates [40,41] or by thermally inducing a buckling transition [42]. In the absence of magnetic field, such a system has been widely investigated in the literature [43][44][45][46][47], with focus on both electronic structure and transport properties in 2D graphene and graphene ribbons or dots. Here, we focus on the case of periodic bumps with a Gaussian profile similar to that of ref.…”
Section: Periodic Bumped Graphene Superlatticementioning
confidence: 99%
“…Confining states within deformed GNR, symmetry properties of LDOS, conductance spectra and pseudospin polarization have been studied in the frame of TB approximation 18 . The effects of an external electric field, the influence of edge roughness on conduction properties of deformed GNRs with centrosymmetric Gaussian bump have been studied using TB model and NEGF transport formalism 19 .
Figure 1 The schematic view of the armchair graphene nanoribbon system.
…”
Section: Introductionmentioning
confidence: 99%
“…The necessary condition to achieve such a conductance property is the existence of sufficiently large energy gap and relatively high conductance outside the gap. We note that recent studies on electron transport properties of GNRs, focused on the energy gap opening mechanism 19 and valley filtering mechanism 6 , are limited to centrosymmetric Gaussian bumps or pure Gaussian folds. In particular, it has been shown that centrosymmetric Gaussian deformation strongly modifies the electronic properties of all types of ribbon structures and leads to a strong reduction of electron transmission in high-energy regions 19 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, the method of converting coal into graphene is basically to change large-particle coal into a precursor carbon source before preparing graphene, and the precursor carbon source can be in the form of molecules, or gas. The preparation method of a precursor carbon source includes the preliminary screening of raw coal, impurity removal, pyrolysis (dry distillation), gasification and liquefaction of coal [ 7 , 8 ]. The usual preparation methods of graphene fabrication from precursor carbon sources include chemical synthesis, mechanical exfoliation, pyrolysis of silicon carbide and chemical vapor deposition [ 9 , 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%